The Impact of Foreign Aid on Income Inequality: Evidence from Developing Countries. Application of the FMOLS Approach - Misbah Nosheen; Sundas Maqbool; Syed Hila Mubarak; Amanat Ali (NUST Journal of Social Sciences and Humanities)
The present study aims to evaluate the impact of foreign assistance on income inequality of selected developing economies. Panel co-integration technique is applied for the purpose of estimation. After confirming the pre-conditions for cointegration, we have applied the Fully Modified-OLS method to estimate the association between foreign aid and income inequality. Controlling for other variables, we find a positive and significant association between foreign aid and inequality. The empirical results are robust concerning the sub-samples of developing economies selected according to the income classification of the World Bank. The empirical results are also robust concerning the alternative measure of income inequality.